A problem solving system employing a formal approach to means - Finnie, Gavin Ross (Department of Computer Science, 2023)
The thesis describes the theory and design of a general problem-solving system. The system uses a single general heuristic based on a formal definition of differences within the framework of means/ends analysis and employs tree search during problem solution. A comparison is made with two other systems using means/ends analysis. The conditions under which the system is capable of solving problems are investigated and the efficiency of the system is considered. The system has solved a variety of problems of varying complexity and the difference heuristic appears comparatively accurate for goal-directed search within certain limits.